Avifauna de las reservas Natural Manejada “El Fisco” y Privada de Uso Múltiple “Isleta Linda”, Santa Fe, Argentina - Fandiño, Blas; Leiva, Leonardo A.; Pautasso, Andrés A.; Luna, Horacio; Manassero, Martín (Nuestras Aves, 2015)
Este artículo no cuenta con un resumen.